HPV Vaccine Uptake, Hesitancy and Information Sources Among Young Adults: A Cross‐Sectional Study of Korea and the US - Soojung Jo; Dongjuan Xu; Hwanseok Song (Health Science Reports, 2026)
ABSTRACT Background and Aims Despite the high effectiveness of HPV vaccination, uptake among young adults remains suboptimal. Healthcare policies, vaccine hesitancy, and sources of vaccine information may contribute to differences in vaccination behaviors across countries. To examine cross‐national and sex‐specific differences in HPV vaccine uptake and hesitancy among undergraduates in the US and Korea, and investigate the role of information sources. Methods This cross‐sectional study targeted undergraduate students in the US and Korea aged between 18 and 25. Data was collected from August 29, 2023, to February 20, 2024 using an online survey through social media exclusive to college students (Korea) and a university listserv (US). A total of 224 survey responses were analyzed after removing missing data ( n = 43). HPV vaccine hesitancy, uptake, and frequency of information source use were assessed. Results HPV vaccine uptake was substantially higher in the US than in Korea (74.0% vs. 33.1%), with a significant sex gap observed only in Korea. Although no significant cross‐national differences in HPV vaccine hesitancy were observed, sex‐specific patterns emerged within each country (OR = 5.3; 95% CI = 1.1–25.3; p = 0.035). In the US, females reported slightly higher hesitancy than males, whereas in Korea, males reported greater hesitancy than females. In multivariable logistic regression, frequent use of social media was associated with higher odds of HPV vaccine hesitancy (OR = 3.3, 95% CI = 1.0–10.4, p = 0.043), while frequent use of professional organizations as an information source was associated with lower odds of hesitancy (OR = 0.4, 95% CI = 0.2–0.9, p = 0.024). Conclusions Tailored public health strategies that address social media's potential role in shaping HPV vaccine hesitancy, while expanded policy support in Korea could improve uptake and reduce hesitancy.